Gastroenterology services: a regional review of changes over a five year period (1981-86). Issue 5 (May 1989) - Scott, B; Atkinson, M
Abstract : A survey of all gastroenterologists in the Trent region showed that the number of upper GI endoscopies had doubled to 7.6 per 1000 of the population from 1981 to 1986, equalling the number of barium meals. Colonoscopies had increased from 0.39 to 0.94 per 1000 of the population. There had been a large increase in the proportion of endoscopies done by surgeons. There were 0.37 ERCP examinations per 1000 of the population done in six of the 12 districts, and 0.17 variceal sclerotherapy procedures per 1000 of the population done in five districts. There was widespread dissatisfaction with the provision of facilities and staff for endoscopy. From 1981 to 1986 the number of consultants with an interest in gastroenterology had increased from 20 to 25, but none of these appointments had been anticipated in 1981. All eight senior registrars in gastroenterology in 1981 had achieved consultant status - three in the region, four in the NHS outside the region, and one abroad.